2000
DOI: 10.1093/hmg/9.10.1495
|View full text |Cite
|
Sign up to set email alerts
|

Loss of DAL-1, a protein 4.1-related tumor suppressor, is an important early event in the pathogenesis of meningiomas

Abstract: Meningiomas are common nervous system tumors, whose molecular pathogenesis is poorly understood. To date, the most frequent genetic alteration detected in these tumors is loss of heterozygosity (LOH) on chromosome 22q. This finding led to the identification of the neurofibromatosis 2 (NF2) tumor suppressor gene on 22q12, which is inactivated in 40% of sporadic meningiomas. The NF2 gene product, merlin (or schwannomin), is a member of the protein 4.1 family of membrane-associated proteins, which also includes e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
131
1
4

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(138 citation statements)
references
References 21 publications
2
131
1
4
Order By: Relevance
“…4.1B is an actin-binding protein involved in actin cytoskeleton organization and actinmediated processes, including cell motility and adhesion. 19,20 It is possible, therefore, to hypothesize that loss of 4.1B function might be involved in metastasis of RCCC cells to distant organs. Our findings that 4.1B promoter methylation is an independent prognostic factor of metastatic recurrence for RCCC patients would support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4.1B is an actin-binding protein involved in actin cytoskeleton organization and actinmediated processes, including cell motility and adhesion. 19,20 It is possible, therefore, to hypothesize that loss of 4.1B function might be involved in metastasis of RCCC cells to distant organs. Our findings that 4.1B promoter methylation is an independent prognostic factor of metastatic recurrence for RCCC patients would support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…1-21 Interestingly, 4.1B/DAL-1 interacts with spectrin, an actin-binding protein, and over expression results in altered cytoskeleton-associated properties, including cell adhesion and motility. 20 To analyze the role of TSLC1 and 4.1B in RCCC, we analyzed 55 surgically resected RCCC and 19 cell lines in the present study. While we could not detect loss of TSLC1 expression, we did find significant alterations in 4.1B gene expression in these tumors.…”
mentioning
confidence: 99%
“…DAL-1 originally was implicated in the tumorigenesis of nonsmall cell lung carcinoma and subsequently has been associated with additional malignancies, including glial tumors, meningiomas, and breast carcinoma. 21,[32][33][34] Recently, Singh et al 20 used both FISH and immunohistochemistry to evaluate 27 ependymomas for NF2/merlin and DAL-1/DAL-1 at the DNA and protein levels, respectively. They found NF2/merlin losses limited to spinal ependymomas, whereas the majority of DAL-1/DAL-1 losses were detected in intracranial lesions.…”
Section: Radiologic Featuresmentioning
confidence: 99%
“…[9][10][11][19][20][21] Secondly, both of these family members are highly expressed in the brain. 22,23 Lastly, we have demonstrated a growth regulatory role for several Protein 4.1 family members in meningiomas, [24][25][26] and preliminary studies have shown that the reintroduction of Protein 4.1R into 4.1R-negative meningioma cell lines results in growth suppression. 27 Based on these observations, we decided to study the Protein 4.1 family members in a larger set of ependymomas.…”
mentioning
confidence: 95%